The Sound and the Fury: Verbal Pre-texts in Vincent Woods’s A Cry from Heaven - Tallone, Giovanna (Hungarian Journal of English and American Studies, 2020)
Vincent Woods’s play, A Cry from Heaven (2005), is an interesting and provocative rewriting in the twenty-first century of the old legend of Deirdre and the Sons of Uisneach, mainly following the Old Irish version, Longes mac N-Uisleann. Unlike the Deirdre plays of the Revival, it stages and exploits the dramatic cry of Deirdre from her mother’s womb.The play has a mixed nature, it is both a pre-text and an after-text, since Woods manipulates the sources and provides twists and variations recounting his own alternative conclusion. At the same time, the play sheds light on language, words, and speech acts as structuring principles. The essay examines the multiple sources of Woods’s play in order to focus on the structuring power of language which characterises the old legend and which plays a relevant role in A Cry from Heaven. (GT)